METODE SYAWIR DALAM PEMBELAJARAN KITAB KUNING DI PONPES NURUL FALAH BERBAUR - Fala, Nurul; Sukawi, Zaenal; Muntaqo, Lutfan (Ta'dib (Jurnal Ilmiah Pendidikan dan Peradaban Islam), 2024)
At the Nurul Falah Berbaur Islamic Boarding School, the deliberation (Syawir) method is routinely applied in the study of yellow books. This activity involves students being divided into groups to discuss specific themes or chapters, with debate sessions deepening understanding of the material. This study used a qualitative approach to evaluate the impact of the Syawir method, which has been shown to improve students' cognitive, affective, and psychomotor abilities, as well as strengthen the social and institutional aspects of the Islamic boarding school. This method also enriches the learning experience, improves the quality of learning, and strengthens social solidarity, making it essential for both personal and institutional development in the Islamic boarding school.